THE TRAINING OF GRATEFULNESS IN IMPROVING LIFE MEANING OF CONVICTS AT CLASS 2 LPKA PEKANBARU - Vivik Shofiah; Khairunnas Rajab (Psikis : Jurnal Psikologi Islami, 2020)
Religious values need are very imporant for convicts at LPKA Class two Pekanbaru. Religion is an obvious influenced source in issuing the meaning of life to convicts. The research objective is to know how far the influence of gratefulness training in improving life meaning of convicts at LPKA class two Pekanbaru is.The researcher used experiment approaching pre and post-test control group designwith 23 control groupsand 23 treatment groups,anddata analysis independent sample t-test was obtained score t= 6,894 (p<0,01). Average score from treatment group are higher (23,057) than control group average (15,6). It shows that life meaning of convicts who get gratefulness training are higher than convicts who don’t join the training. With thus, it can be concluded that gratefulness training very influence significantly to the life meaning of convicts at LPKA class 2 Pekanbaru.